Free will beliefs predict attitudes toward unethical behavior and criminal punishment - Martin, Nathan D. (Proc Natl Acad Sci U S A, 2017)
Do free will beliefs influence moral judgments? Answers to this question from theoretical and empirical perspectives are controversial. This study attempted to replicate past research and offer theoretical insights by analyzing World Values Survey data from residents of 46 countries (n = 65,111 persons). Corroborating experimental findings, free will beliefs predicted intolerance of unethical behaviors and support for severe criminal punishment. Further, the link between free will beliefs and intolerance of unethical behavior was moderated by variations in countries’ institutional integrity, defined as the degree to which countries had accountable, corruption-free public sectors. Free will beliefs predicted intolerance of unethical behaviors for residents of countries with high and moderate institutional integrity, but this correlation was not seen for countries with low institutional integrity. Free will beliefs predicted support for criminal punishment regardless of countries’ institutional integrity. Results were robust across different operationalizations of institutional integrity and with or without statistical control variables.